Determination Of The Effect Of Ph On Microalagal Growth And Protein Content In Locally Isolated Tetraselmis Suecica And Scenedesmus Parvus - Chuen Yeong, Kah (Pusat Pengajian Teknologi Industri, 2020)
Mass production of certain protein rich microalgae as single cell protein was considered as a possibility to minimise the protein gap due to increasing of global population. However, the protein productivity and the growth of the microalgae will be affected by the cultivation condition during the mass production. Thus, this project is to explore the possibility of the locally isolated microalgae as a single cell protein source where both microalgae Tetraselmis suecica and Scenedesmus parvus were cultivated in different initial pH cultivation medium (pH 3.00 to pH 9.00). The growth kinetic and growth profile of the microalgae over 13 day’s cultivation period were determined. The protein content as well as the protein productivity of the microalgae biomass were determined using Kjeldahl method. Lastly, suitable kinetic growth model for both microalgae under different pH medium was also determined among Logistic model, Gompertz model and Baranyi-Roberts model. The maximum biomass concentration and highest biomass productivity for T. suecica was obtain at pH 5.00 with 157.842 ±4.507 mg L-1 and 9.767 ±0.003 mg L-1d-1 respectively while maximum biomass concentration and highest biomass productivity for S. parvus was obtain at pH 7.00 with 154.447 ± 3.030 mg L-1 and 10.132 ± 0239 mg L-1d-1 respectively. The maximum protein content and highest protein productivity of T. suecica was obtained at pH 5.00 with 44.704 ±0.785 % and 4.366 ±0077 mg L-1d-1 while maximum protein content and highest protein productivity of S. parvus were obtained at pH 7.00 with 36.93 ±1.039 % and 3.742 ±0.105 mg L-1d-1respectively.